Analysis of temporomandibular joint dysfunction in paediatric patients with unilateral crossbite using automatically generated finite element models. Issue 10 (26th July 2020) - Ortún-Terrazas, Javier; Cegoñino, José; Illipronti-Filho, Edson; Pérez del Palomar, Amaya
Abstract: The evaluation of temporomandibular joint (TMJ) dysfunction using finite element models is a time consuming process that requires extensive technical knowledge. We combined a statistical active appearance model with automated modelling algorithms to biomechanically study the relationship between TMJ malformations and dysfunction in radiographs from 20 paediatric patients with unilateral crossbite. A fitting algorithm (fitting error < 4%) recognised the TMJ shape and adjusted the dimensions of each patient-specific 2D FE model, which was then used to compute 2 different joint movements. Significant functional differences were observed between the crossbite and non-cross bite sides, and the shape-function relation was verified.